Building and standardizing a composite test in terms of ability (mental and skill) to select the emerging players in the fencing sport Emaar (14-16) years - أ.د حامد سليمان حمد م.م وائل علاءالدين حسون (physical education and sport sciences college for women/ Baghdad University, 2018)
In order to achieve these objectives, the sample of the research, which included the 98 players in Iraq, was determined and distributed as follows: 20 sample survey sample, 64 sample building players, 78 sample of the standardization tests conducted by the main experiment.The researcher designed a test whose validity has been ascertained and scientific studies (honesty, consistency and objectivity) as well as its ability to discriminate and the appropriate statistical treatment has been carried out to be applied to the standardization sample to find the standard and standard level and compare it with the normal distribution level (KAOS) In addition, the composite test of mental ability has led to a significant weakness in this ability. The researcher recommends the adoption of the research test in the process of selecting the youth with the age of 14-16 years, Which was reached as a result of the research in the selection process and the testing of all age groups of fencing.